Enhancing IT Employee Placement Using SMARTER with Centroid Rank Order Weighting for Candidate Suitability - Ben Rahman; Saskia Adinda; Adelia Putri Handayani (LPPM Universitas Islam 45 Bekasi, 2024)
In an era characterized by constant evolution in digital technology, the significance of Information Technology (IT) within organizations is of utmost importance. Efficient recruitment processes and appropriate placement of IT personnel are crucial for a company's success. This research aims to develop a candidate assessment system using the SMARTER (Smart Simple Multi-Attribute Rating Technique Exploiting Rank) approach combined with the Rank Order Centroid weighting method to assist HR departments in selecting suitable IT candidates. Addressing the challenges faced by HR directors lacking IT expertise, this study offers an innovative solution to enhance alignment between candidates and IT position requirements. Through the analysis of nine specific criteria, including education, work experience, and English proficiency, the system is designed to provide more accurate candidate placement recommendations. The findings of this research demonstrate significant potential in improving IT recruitment processes and contributing significantly to the literature.